2017
DOI: 10.1128/aac.02071-16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum-β-Lactamase- and/or Carbapenemase-Producing Escherichia coli Isolated from Yellow-Legged Gulls from Barcelona, Spain

Abstract: Seventy-two (54.5%) out of 132 fecal samples from a group of yellowlegged gulls in Barcelona, Spain, were positive for Escherichia coli producing either extended-spectrum ␤-lactamases (ESBL) (51.5%), carbapenemase (1.5%), or cephamycinase (1.5%). The isolation of two carbapenemase-producing E. coli strains is a matter of concern.KEYWORDS carbapenemases, E. coli, ESBL I n the last decade, the number of bacterial pathogens presenting multidrug resistance to antibacterial agents has increased dramatically, becomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
1
22
2
1
Order By: Relevance
“…Wildlife acquires CRE for example by contact with sewage, manure, or waste disposal sites [93]. Importantly, we found several reports describing CRE in swallows, black kites, storks, or gulls (with a high prevalence in France and Australia), demonstrating that these birds may act as reservoirs for bla NDM , bla OXA-48 , bla IMP , bla VIM-1 , and bla KPC-2 [25,78,79,82,83,85]. These findings raise concern because they indicate that these carbapenemases are prevalent in the environment in amounts that not only lead to colonization of wildlife, but also because these (migratory) birds may act as vectors facilitating the spread of CRE beyond borders of farms, dwelling zones, countries, or even continents.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Wildlife acquires CRE for example by contact with sewage, manure, or waste disposal sites [93]. Importantly, we found several reports describing CRE in swallows, black kites, storks, or gulls (with a high prevalence in France and Australia), demonstrating that these birds may act as reservoirs for bla NDM , bla OXA-48 , bla IMP , bla VIM-1 , and bla KPC-2 [25,78,79,82,83,85]. These findings raise concern because they indicate that these carbapenemases are prevalent in the environment in amounts that not only lead to colonization of wildlife, but also because these (migratory) birds may act as vectors facilitating the spread of CRE beyond borders of farms, dwelling zones, countries, or even continents.…”
Section: Discussionmentioning
confidence: 61%
“…3. As shown in Tables 2 and S3, CRE isolates harbouring bla OXA-48 , bla NDM-1 , bla NDM-5 , bla NDM-9 , or bla-VIM-1 were detected in dogs [25,67,68,70e75], bla OXA-48 , bla IMP-4 , or bla NDM-1 in cats [67e69, 71,74,75], bla OXA-48 in horses [68,71], bla OXA-48 in pet birds [68], bla NDM-1 and bla NDM-5 in swallows [25], bla OXA-48 in wild boars [77], bla OXA-48 in wild storks [78], bla IMP , bla VIM-1 , and bla KPC-2 in silver and yellow-legged gulls [79,82,85] and bla NDM-1 in a black kite [83]. Carbapenemase-encoding genes were found in the following bacterial species isolated from companion animals and wildlife: E. coli (bla OXA-48 , bla NDM-1 , bla NDM-5 , bla NDM-9 , bla IMP-4 , bla VIM-1 , bla KPC-2 ), Klebsiella spp.…”
Section: Occurrence Of Cre In Companion Animals and Wildlifementioning
confidence: 99%
“…Our study revealed frequent occurrence of carbapenemase- and ESBL-producing Enterobacteriaceae (16% and 55%, respectively) colonizing gulls from the Lisbon coastline, Portugal. ESBL-producing Enterobacteriaceae among gulls were previously reported in USA [ 6 ], Canada [ 4 ], Chile [ 5 ], and in different countries in Europe [ 8 , 31 , 32 , 33 , 34 ], including Portugal in 2008 [ 12 , 13 ]. The high heterogeneity observed here in terms of bacterial species, ST, and resistance determinants showed that the high resistance rates observed were basically not simply consequences of shared microbiota between bird individuals, that could have biased our observation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, gulls have been reported as carriers of ESBL-producing E. coli in Europe, South America, North America, and Asia [ 2 , 3 , 4 , 5 , 6 ]. More recently, a very limited number of studies documented fecal carriage of carbapenemase-producers in gulls in Spain, France, Australia, and Alaska, being exclusively E. coli [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large populations of YLGs have been often associated with negative effects on other syntopic bird species via predation, kleptoparasitism and competition for nesting places (Vidal et al , Oro and Martínez‐Abraín , Paracuellos and Nevado ). In addition, gull‐human conflicts associated to their bold behavior and their role as a potential vector for human pathogens, such as Escherichia coli , might arise due to the usual vicinity of breeding sites to human settlements (Vergara et al ). These issues have raised concerns to the point that several countries have undergone management actions to reduce population size (Bosch et al , Steigerwald et al ).…”
mentioning
confidence: 99%